Prediction, prevention, and mechanism of early (anaphylactic) antivenom reactions in victims of snake bites. - Malasit, P; Warrell, D; Chanthavanich, P; Viravan, C; Mongkolsapaya, J; Singhthong, B; Supich, C (1986)
Victims of snake bites are often subjected to cutaneous or conjunctival hypersensitivity testing before being given antivenom. None of 12 early (anaphylactic) reactions was predicted by these tests in 25 Nigerian and Thai patients. The incidence and severity of early reactions was the same whether antivenom was given by intravenous injection over 10 minutes or diluted and given as an intravenous infusion over 30 minutes. Although antivenom activated complement in vitro, there was no evidence of complement activation or formation of immune complexes in patients bitten by snakes who were treated with antivenom, whether or not they developed early reactions. Higher doses of antivenom might induce the complement activation and formation of immune complexes (aggregates) that have been observed during the clinically more severe reactions associated with homologous immunoglobulin treatment.